Metode Pendidikan Karakter Melalui Pengajaran Moral Pencipta dan Sesama Manusia Anak Usia 5-6 Tahun di TK Islam Al-Izhar Cendekia Makassar - Islami, Andi Nur Maharani; Bachtiar, Muhammad Yusri; Yusran, Ramlah (Ihya Ulum: Early Childhood Education Journal, 2024)
Character education is a form of effort and service in the field of education provided to children with the aim of helping their growth and development process physically and mentally. Character education refers to efforts in education that aim to support children's physical and mental development. This process is carried out by providing stimulation related to attitudes, knowledge, and basic skills combined with character education, which is designed to be appropriate to the context and environment in which the child is located. This study was conducted using a qualitative descriptive method approach to describe the observed phenomena in depth. The title raised by the researcher is "Initial Steps in Character Education: Teaching Respect for God and the People Around Them to Children Aged 5-6 Years at Al-Izhar Cendekia Islamic Kindergarten Makassar." In this study, children, teachers, and principals were used as the main objects for data collection and analysis. The results of this study revealed that most children were able to demonstrate behavior in accordance with the objectives of character education that had been implemented. They also showed the ability to focus while performing prayers calmly, indicating the success of the learning process that emphasizes respect for God and the people around them.